Topological design of structures under dynamic periodic loads. (1st July 2017) - Liu, Baoshou; Huang, Xiaodong; Huang, Changfu; Sun, Guangyong; Yan, Xiaolei; Li, Guangyao
Highlights: Topology optimization of structures under periodic dynamic forces is developed based on the BESO update scheme. Various solid-void optimized design with clear topologies are obtained. Topology optimization problems for different scenarios are presented. Abstract: Most of forces acted on real structures are dynamic and topology optimization of dynamic structures has aroused wide attention over the past years. Due to the complexity of dynamic behavior, achieving clear 0/1 optimal topology of dynamic structures is still challenging. This paper aims to develop a topology optimization algorithm of dynamic structures under periodic loads based on the bi-directional evolutionary structural optimization (BESO) method. To minimize the dynamic compliance under the single or multiple excitation frequencies, four typical topology optimization problems are proposed for different scenarios. To solve the defined topology optimization problems, sensitivity analysis with regard to the variation of design variables is conducted for iteratively updating the structural topology. Since BESO uses discrete design variables, the resulting solid-void solutions show unambiguous topologies of dynamic structures. Various 2D and 3D numerical examples are given to demonstrate the capability of the proposed method for obtaining optimal designs of dynamic structures under periodic loads.